FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN MAKANAN SIAP SAJI PADA KFC JALAN GAJAH MADA MEDAN - Arlita Citra Sinambela; Rindi Andika; Hasrul Azwar Hasibuan (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
This study aims to determine the effect of product, price, location, and service partially and simultaneously on the decision to buy fast food at KFC Jalan Gajah Mada Medan. The form of research used is quantitative research. The data used is primary data. This study uses 100 respondents as the research sample and the sample selection technique is Accendential Sampling with the criteria of consumers who have made purchases to KFC Jalan Gajah Mada Medan. The data analysis technique used is instrument test (validity and reliability) and multiple linear regression analysis. Based on the results of the research that has been done, the results show that the product, price, location, and service partially have a positive and significant effect on consumer behavior in making decisions to buy fast food at KFC Jalan Gajah Mada Medan. Product, price, location, and service simultaneously have a positive and significant effect on the decision to buy fast food at KFC Jalan Gajah Mada Medan.Keywords: Product, Price, Location, Service and Purchase Decision.